First assessment of leaf lipids and fatty acids as biomarkers of grapevine tolerance/susceptibility to Plasmopara viticola. (March 2023) - Cavaco, Ana Rita; Laureano, Gonçalo; Duarte, Bernardo; Marques da Silva, Jorge; Gameiro, Carla; Cunha, Jorge; Eiras Dias, José; Matos, Ana Rita; Figueiredo, Andreia
Abstract: Grapevine is susceptible to several diseases, being downy mildew, caused by Plasmopara viticola, among the most devastating. Control strategies include the application of pesticides every season through almost all the grapevine developmental stages, jeopardizing viticulture sustainability. Understanding resistance molecular processes is crucial to define alternative strategies and select disease resistance traits. Identifying markers that discriminate between tolerant and susceptible genotypes to P. viticola is an important step. It is shown that lipids and fatty acids (FA) play an important role in grapevine defence against downy mildew and in our previous works we have highlighted that susceptible and resistant grapevine genotypes present contrasting FA profiles even without infection. Here, the constitutive lipid and FA composition of four grapevine genotypes, with contrasting behaviour toward P. viticola was analysed. FA desaturases (FAD) gene expression was also analysed. The results indicate that the susceptible genotypes present higher content of plastidial lipids and unsaturated FA and higher expression levels of FAD genes, whereas tolerant genotypes have higher amounts of neutral lipids and phosphatidic acid as well as saturated FA. In this preliminary study, the concentration of monogalactosyldiacylglycerol and phosphatidylcholine was pinpointed as potential tolerance-associated biomarkers and both linoleic acid and plastidial lipids as susceptibility-associated biomarkers. Highlights: Lipids and fatty acid desaturase genes are grapevine tolerance/susceptibility markers to Plasmopara viticola. Susceptible genotypes have higher plastid lipids, unsaturated fatty acids and fatty acid desaturase expression levels. Tolerant genotypes have higher neutral lipids, phosphatidic acid and saturated fatty acid amounts.